Nutritients depictions of Barhi date palm (Phoenix dactylifera L.) kernels 1 - Mahmud, Mohammed Imad A. Mustafa; Mirghani, Mohamed Elwathig Saeed; Al-Khatib, Ma'an Fahmi Rashid; Yusof, Faridah; Muhammad Nur Azraei, Shahabudin; Othman, Rashidi; Daoud, Jamal Ibrahim (Universiti Putra Malaysia Press, 2017)
Phoenix dactylifera L (Date palm) is one of the oldest known fruit crops in the world, 14